Desarrollo de un sistema de medición de caudal energéticamente independiente con transmisión de datos en la comunidad de Paquiestancia. - Campoverde Cueva, Carlos Gabriel (2018)
In the Community Paquiestancia there distribution of water for irrigation in different plots, this is done by pipes 1 inch for different pastures, there inappropriate consumption of water, is the need for flow measurement in said pipe to have a consumption control. The purpose of this project is to visualize the flow that passes through a 1-inch pipe, whose data will be sent to a service in the cloud to be displayed on a web page and an application for mobile device to the president of the Irrigation Board of the Community of Paquiestancia. After analyzing the system was determined for this project type vortex flowmeter LVB-25 since it is the ideal, so that water is not completely pure, this sensor has the advantages of having digital output and another analogy current 4 20 mA. The signals obtained from the flow meter are oscillation frequencies, delivered by the internal mechanical sensor thereof, which are transformed into a current output giving a linear signal directly proportional to the fluid flow rate. This signal will be monitored and sent to a service in the cloud and in addition the same data is sent to an Android app for mobile device and to a web page.